Third‐Trimester Abnormal Uterine Artery Doppler Findings Are Associated With Adverse Pregnancy Outcomes. (1st December 2013) - Shwarzman, Polina; Waintraub, Adi Y.; Frieger, Michael; Bashiri, Asher; Mazor, Moshe; Hershkovitz, Reli
Abstract : Objectives: To evaluate the association between third‐trimester abnormal uterine artery Doppler findings and pregnancy outcomes. Methods: A prospective study was designed, including 198 consecutive singleton pregnancies between 27 and 41 weeks' gestation. In the study population, 144 had normal uterine artery Doppler waveforms, 37 had unilateral pathologic waveforms, and 17 had bilateral pathologic waveforms. Eighty patients had intrauterine growth restriction (IUGR), preeclampsia toxemia, or both, and 118 had no complications and served as a control group. The uterine artery Doppler waveform was considered abnormal when a notch or pulsatility index above the 90th percentile was noted. Results: In patients with bilateral pathologic uterine artery Doppler waveforms, the rates of cesarean delivery, small‐for‐gestational‐age (SGA) neonates, preterm delivery, and low Apgar scores were increased compared to patients with normal or pathologic unilateral waveforms ( P = .009; P > .001; P = .007; P > .001, respectively). The incidence rates for SGA neonates, cesarean delivery, and preterm delivery were significantly higher among patients without IUGR or preeclampsia toxemia when associated with pathologic bilateral waveforms in comparison to normal waveforms ( P = .01 for all). A bilateral pathologic waveform was found to be an independent risk factor for cesarean delivery and SGA neonates. The incidence rates for SGA neonates and preterm delivery were significantly higher among patients with IUGR and/or preeclampsia toxemia when associated with bilateral abnormalities in comparison to normal waveforms ( P = .01 for both). Conclusions: Third‐trimester abnormal uterine artery Doppler findings are associated with worse perinatal outcomes among patients both with and without pregnancy complications.